(untitled) (Scientific journal of the Fergana State University, 2023)
In this article the liberation of the Ferghana valley from the Mongolian invaders and it’s inclusion in the structure of Amir Temur’s Empire, the relationship of this process with successes in foreign policy, created new administrative units and their heads are analyzed.